2016
DOI: 10.29173/iq902
|View full text |Cite
|
Sign up to set email alerts
|

New Curation Software: Step-by-Step Preparation of Social Science Data and Code for Publication and Preservation

Abstract: New Curation Software: Step-by-Step Preparation of Social Science Data and Code for Publication and Preservation

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…Code review and reproducibility verification, for example, One mechanism that can help implement steps in this typical workflow is the Yale Application for Research Data (YARD). YARD manages and tracks metadata production and other quality review activities that contribute to a "FAIRer" research and exposes the review process to scrutiny [15,16]. Figure 2 illustrates the actions of both machine and human actors (i.e., curators and authors) and the interactions between these two types of actors.…”
Section: Efforts To Ensure the Reproducibility Of Published Research ...mentioning
confidence: 99%
“…Code review and reproducibility verification, for example, One mechanism that can help implement steps in this typical workflow is the Yale Application for Research Data (YARD). YARD manages and tracks metadata production and other quality review activities that contribute to a "FAIRer" research and exposes the review process to scrutiny [15,16]. Figure 2 illustrates the actions of both machine and human actors (i.e., curators and authors) and the interactions between these two types of actors.…”
Section: Efforts To Ensure the Reproducibility Of Published Research ...mentioning
confidence: 99%
“…For example, YARD prompts Curators to review whether documentation and contextual information necessary for long-term usability (e.g., a codebook, a readme file) are included. The curation workflow has been further enhanced to include tasks for reviewing code and statistical analysis to obtain verification of computational reproducibility (Peer & Wykstra, 2015;Peer, 2017). For example, YARD guides Curators to review code files -statistical and other programming scripts -by verifying that the code executes and that the published scientific results can be computationally reproduced with the given code and data.…”
Section: The Curation Workflowmentioning
confidence: 99%
“…In 2010, Cushing identified PDA as an area of activity that intersects with both PIM and with records management. Given the recent interest in transparency for the research process, observed by Peer and Wykstra (2015) to have begun roughly ten years ago, a good deal of attention is currently being devoted to the topic of RDM in the scholarly communications community. RDM is clearly a topic that stands to have a good deal of overlap with PDA in academic environments.…”
Section: Rdm and Pimmentioning
confidence: 99%